Good governance in rural local administration - Zaitul Zaitul; Desi Ilona; Neva Novianti (Administrative Sciences, 2023)
The governance principle is an important aspect of good governance, and its implementation is believed to have a good impact on governance outcomes, such as corruption reduction and performance improvement. The governance principle has been developed for several types of organisations. However, previous studies did not focus on the rural local administration's governance. This study aims to develop a good governance principle for the rural local administration. There are four objectives of this study: first, to identify governance principles and their indicators in the literature; second, to create a governance principle using exploratory factor analysis; third, to model the governance principle using the structural equation model (SEM); and finally, to analyse any different perceptions about the governance principles for the rural local administration using univariate analysis. The result showed that 33 indicators of governance principles were identified through the literature. Using 238 usable questionnaires and exploratory factor analysis, we found 6 governance principles: fairness and capability, inclusivity, legitimacy and direction, participation, performance and information, and transparency and accountability. Using the second-order SEM in SmartPLS, we developed a governance principle model for the rural local administration. A few indicators of governance principles found were deleted through measurement model validation. In addition, the univariate analysis concluded that perceptions did not differ by the sex, education level, and occupation type of respondents. In other words, they agreed with the governance principle for the rural local administration. This study has practical and theoretical implications, which are discussed in detail in this article.
Keywords: 350; good governance principle; Indonesia; rural local administration